Zur Rezeption der Gestalt des Judas Iskariot im Islam und im Judentum. Ein Versuch der Annäherung an ein heikles Thema (Teil I) - Heindl, Andreas (Protokolle zur Bibel, 2006)
Judas Iscariot, one of the most controversial characters in the NT, invited - and still invites - to discussion beyond the bounds of Christianity. One tradition of Islamic exegesis of the hardly intelligible Koran Sura 4.157f. claims that God gave the traitor of Jesus his appearance, whereupon he was crucified in his master’s place. This tradition is inter alia represented by the so-called „Gospel of Barnabas“. Herein Judas is shown at his worst: as an infidel, a greedy thief possessed by the devil. God saves Jesus from his impending arrest by having him carried away to heaven by his four archangels. Judas receives Jesus’ outward appearance, which results in his passion, the latter being described in awfully great detail.